Pentingnya Penguasaan Bahasa Arab dalam Pembelajaran Pendidikan Islam - Arisnaini, Arisnaini (Universitas Serambi Mekkah, 2024)
Arabic is one of the languages of communication and also the language of religion. therefore most Muslims learn Arabic to make it easier to understand the contents of the holy book Al- Qur'an 'an and to explore the religious side. This research is a library research (Library Research). The library method is a suitable method in this research. Because in this case library sources such as books and journals will be used to collect various data relating to instilling the values of monotheism in learning Arabic. This study aims to determine the importance of understanding the Arabic language. Learning Arabic requires carefulness and seriousness since the tools of knowledge acquired in Arabic will not be easily understood in a short learning times. Therefore, one who wants to understand Islam well is highly recommended to study Arabic seriously as the most impossible thing he can do. That is because by learning Arabic, he will be able to understand every meaning of Islamic teachings contained in the holy book Al- Qur'an which has been written in Arabic. The results of this study indicate that there is an urgency to learn Arabic in the realm of Islamic education when viewed from the perspective of human life, structurally related to cultural tools.